Optical frequency domain imaging system and catheters for volumetric imaging of the human esophagus - Gora, Michalina; Yoo, Hongki; Suter, Melissa J; Gallagher, Kevin A; Bouma, Brett E; Nishioka, Norm S; Tearney, Guillermo J (Photonics Letters of Poland, 2011)
Barrett’s esophagus (BE) is a metaplastic disorder that can undergo dysplastic progression, leading to esophageal adenocarcinoma. Upper endoscopy is the standard of care for screening for BE, but this technique has a relatively low diagnostic accuracy and high cost due to the requirement of conscious sedation. Optical frequency domain imaging (OFDI) is a high-speed imaging modality that generates cross-sectional images of tissues with a resolution of approximately 10µm that is sufficient for detecting microscopic tissue architecture. In combination with a balloon-centering catheter, this method enables BE diagnosis over the entire distal esophagus. Full Text: PDF References S. H. Yun et al.,"High-speed optical frequency-domain imaging", Opt. Exp. 11, 2953 (2003)[CrossRef] J.G. Fujimoto et al.,"Optical biopsy and imaging using optical coherence tomography", Nat. Med. 1, 9 (1995)[CrossRef] G. Zuccaro et al.,"Optical coherence tomography of the esophagus and proximal stomach in health and disease", Am. J. Gastroenterol. 96, 9 (2001)[CrossRef] X. Qi et al.,"Computer-aided diagnosis of dysplasia in Barrett?s esophagus using endoscopic optical coherence tomography", J. Biomed. Opt. 11, 4 (2006)[CrossRef] Y. Chen et al.,"Ultrahigh resolution optical coherence tomography of Barrett’s esophagus: preliminary descriptive clinical study correlating images with histology", Endoscopy 39, 7 (2007)[CrossRef] M. J. Suter et al.,"Comprehensive microscopy of the esophagus in human patients with optical frequency domain imaging", Gastrointest Endosc. 68, 4 (2008)[CrossRef] M. J. Cobb et al.,"Imaging of subsquamous Barrett’s epithelium with ultrahigh-resolution optical coherence tomography: a histologic correlation study", Gastrointest. Endosc. 71, 2 (2010)[CrossRef] R. C. Haggitt et al.,"Barrett’s esophagus, dysplasia, and adenocarcinoma", Human Pathology 25, 10 (1994)[CrossRef] L. M. Brown et al.,"Incidence of Adenocarcinoma of the Esophagus Among White Americans by Sex, Stage, and Age", [CrossRef] R. F. Souza et al.,"Concepts in the Prevention of Adenocarcinoma of the Distal Esophagus and Proximal Stomach", CA: A Cancer J. Clin. 55, 6 (2005)[CrossRef] B. E. Bouma et al.,"Power-efficient nonreciprocal interferometer and linear-scanning fiber-optic catheter for optical coherence tomography", Opt. Lett. 24, 531 (1999)[CrossRef] W. Kang et al.,"Endoscopically guided spectral-domain OCT with double-balloon catheters", Opt. Exp. 18, 17364 (2010)[CrossRef]